Deconstruction of The Code of Ethics for Public Accountants Based on Siri Culture - Jalal Ikram, Abdi Dzul; Triyuwono, Iwan; Baridwan, Zaki (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
The research aims to formulate a code of ethics for public accountants based on siri 'culture. This research will deconstruct the code of ethics for Indonesian public accountants and instill siri' principles. This research instills local wisdom values into the code of ethics and gives birth to the concept of a new code of ethics with local wisdom culture in it. This research uses literature studies. The technique for analyzing data in this research uses the Pabbotting method. Pabbotting is a traditional term for uniting bridal couples in the Bugis tribe. The results of this research combine the principles of Siri 'culture with the code of ethics for public accountants, directing accountants to comply with the basic principles of the existing code of ethics for public accountants. Siri' culture also functions to help public accountants solve local problems in Indonesia.